Evaluating the safety and effectiveness of percutaneous acetabuloplasty. (6th April 2011) - Gupta, Amar C; Hirsch, Joshua A; Chaudhry, Zeshan A; Chandra, Ronil V; Pulli, Benjamin; Galinsky, Janice G; Hirsch, Ariel E; Yoo, Albert J
Abstract : Purpose: To evaluate the safety and effectiveness of percutaneous acetabuloplasty in treating the pain and disability related to metastatic lesions of the acetabulum. Materials and methods: This institutional review board approved retrospective study examined 11 patients who underwent percutaneous acetabuloplasty in our hospital from April 2007 to June 2010. All patients gave informed consent prior to the procedure, and all records were HIPAA compliant. Chart review was performed to collect patient demographics and to assess pre- and post-treatment patient performance on the Visual Analog Scale, Functional Mobility Scale and Analgesic Scale. Paired testing comparing the pre- and post-treatment scores for each patient was performed using the Wilcoxon signed rank test. Results: There were 11 procedures: 10 performed under CT guidance and one using fluoroscopic guidance. There was a statistically significant decrease in patient Visual Analog Scale score (p=0.001) and Functional Mobility Scale score (p=0.03) after treatment. There was no change in median Analgesic Scale scores pre- and post-treatment although paired testing revealed a trend towards reduced analgesic use postoperatively (p=0.06). There were no clinically significant complications in this series. Conclusion: Percutaneous acetabuloplasty appears to be safe and effective for improving the pain and decreased mobility secondary to metastatic lesions of the acetabulum.